Unveiling the determinants of the spatial variability of nitrogen sources use in the Lake Victoria basin, East Africa - Catherine Mathenge; Stephen Mureithi; Soul-Kifouly Midingoyi; Benjamin Nyilitya; Geoffrey Kironchi; Cargele Masso (Environmental and Sustainability Indicators)
As nitrogen pollution increasingly threatens water quality in the Lake Victoria Basin, it is essential to investigate the spatial factors influencing nitrogen source use. Understanding these determinants is crucial to inform effective strategies to combat eutrophication, enhance nutrient management, ensure food security and promote sustainable ecological development. This study investigated spatial variation of N sources, the farmers' socio-demographic and farm characteristics factors influencing farmers' choice of nitrogen sources. Data was collected from 1500 farmers between October and December 2020. The farmers were randomly selected in Kenya, Rwanda, Uganda, Burundi and Tanzania country sub-basins within the Lake Victoria basin (LVB). Spatial autocorrelation was used to evaluate the spatial variation of the nitrogen sources while the Optimized Parameter Geographical Detector (OPGD) model was used to identify the factors influencing the choice or use of N sources. The OPDG results indicate that the country of residence and livestock ownership are the primary factors accounting for 31.9% and 22.1% of the variation in nitrogen sources across the entire Lake Victoria Basin, respectively. The major sub-basin factors influencing the use of N sources were both farm characteristics (types of crops grown and farm size) and social socio-demographic factors of the farmer (education). These findings highlight the need for tailored strategies, accounting for geographical variations, farm characteristics and socio-demographic factors are essential when formulating nitrogen management strategies and policies at local and regional scales within the LVB.